PENGARUH PUPUK KANDANG KOTORAN SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG TANAH (Arachis hypogaea L.) - Suhaeni; Safitri Sacita, Andi; Rante Tondok, Yusriadi (Universitas Cokroaminoto Palopo, 2024)
This research aims to determine the effectiveness and correct dosage of applying cow dung manure on the growth and production of peanut plants. This research was carried out at the experimental field of the Faculty of Agriculture, Cokroaminoto Palopo University, Jalan Lamaranginang, Batupasi Village, North Wara District, Palopo City, in the month March to May 2022. This research method uses a Randomized Block Design (RAK) consisting of 6 treatments and 4 replications. The treatment with P0= control, P1= 100 gr cow manure, P2= 200 gr cow manure, P3= 300 gr cow manure, P4= 400 gr cow manure, P5= 500 gr cow manure gr. The results of this study showed that the application of cow dung manure and straw mulch showed the best results in treatment P5 with the highest parameters in plant height with an average of 59.45 cm, number of leaves with an average of 263, flowering age with an average of 41. .25 days, the number of pods was an average of 80.75 pods, and the weight of the pods was an average of 226.25 grams at a treatment dose of 500 grams of cow dung manure and 1 kg of straw mulch. Based on the research results obtained, it can be concluded that the application of cow dung manure has a significant effect on the parameters of plant height, number of leaves, flowering age, number of pods and pod weight. This is thought to be due to the nutrients N, P and K contained in cow manure